Core social motives explain responses to collective action issues. Issue 3 (16th January 2023) - Geiger, Nathaniel; Brick, Cameron
Abstract: Managing collective action issues such as pandemics and climate change requires major social and behavioral change. Dominant approaches to addressing these issues center around information provision and financial incentives to shift behavior, yet, these approaches are rarely effective without integrating insights from psychological research on motivation. By accurately characterizing human motives, social scientists can identify when and why individuals engage, and facilitate behavior change and public engagement. Here, we use the core social motives model to sort social psychological theories into five fundamental social motives: to Belong, Understand, Control, self‐Enhance, and Trust. We explain how each motive can improve or worsen collective action issues, and how this framework can be further developed towards a comprehensive social psychological perspective to collective action issues.